2012
DOI: 10.4103/0189-6725.104721
|View full text |Cite
|
Sign up to set email alerts
|

Collaboration between paediatric surgery and other medical specialties in Nigeria

Abstract: There is presently inadequate collaboration between paediatric surgery and other specialties in Nigeria. There is a need for more inter-specialty support, communication, and exchange of ideas in order to achieve desirable outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
0
0
1
Order By: Relevance
“…For example, nearly all the paediatric surgeons (92%, n=41) surveyed in a recent study by Ameh and Ekenze identified communication skills with colleagues and families as an essential aspect of paediatric surgery training. [8] Yet, in the current study by Okoro et al [1] a similar proportion of paediatric surgeons (95.7%, n=45) report inadequate collaboration with other specialties. Once again, noble aspiration meets the hard reality of a medical practice culture that sometimes retards progress.…”
contrasting
confidence: 58%
“…For example, nearly all the paediatric surgeons (92%, n=41) surveyed in a recent study by Ameh and Ekenze identified communication skills with colleagues and families as an essential aspect of paediatric surgery training. [8] Yet, in the current study by Okoro et al [1] a similar proportion of paediatric surgeons (95.7%, n=45) report inadequate collaboration with other specialties. Once again, noble aspiration meets the hard reality of a medical practice culture that sometimes retards progress.…”
contrasting
confidence: 58%